2017
DOI: 10.1002/pssa.201700373
|View full text |Cite
|
Sign up to set email alerts
|

Saw Damage Gettering for industrially relevant mc‐Si feedstock

Abstract: The silicon photovoltaic industry is currently shifting towards lightly doped emitters. These have electrical properties that benefit solar cells, compared to the traditional heavily doped emitters. This move brings new challenges, as gettering efficiencies of impurities are lowered as the doping reduces. This is particularly problematic in multicrystalline silicon (mc-Si) since cell performance is typically boosted by the effective gettering of such impurities. In prior work, we proposed the novel gettering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
0
14
1
Order By: Relevance
“…They fabricated sacrificial porous silicon (PS) layers on Si wafers and demonstrated that the harmful impurities were gettered from the bulk material to the porous layer during thermal annealing due to the high surface reactivity of PS. Similarly, mechanical 19 or saw damage 20 , 21 has been used as effective gettering sites. Thus, b-Si could promote the removal of impurities via near-surface precipitation, in addition to enhanced segregation.…”
Section: Introductionmentioning
confidence: 99%
“…They fabricated sacrificial porous silicon (PS) layers on Si wafers and demonstrated that the harmful impurities were gettered from the bulk material to the porous layer during thermal annealing due to the high surface reactivity of PS. Similarly, mechanical 19 or saw damage 20 , 21 has been used as effective gettering sites. Thus, b-Si could promote the removal of impurities via near-surface precipitation, in addition to enhanced segregation.…”
Section: Introductionmentioning
confidence: 99%
“… is probably the most similar to our material, although it is likely to have a lower dislocation density than our top material. For this material, average lifetime improved from ∼10 to 37 μs by SDG at 850 °C . Considering just the samples annealed at ≥500 °C for reasons discussed above, our best lifetime after SDG was 25.2 μs at 600 °C which is an improvement of 63% relative to the average as‐received lifetime in sister samples (15.5 μs).…”
mentioning
confidence: 67%
“…The “standard performance bottom red zone” used in Ref. is probably the most similar to our material, although it is likely to have a lower dislocation density than our top material. For this material, average lifetime improved from ∼10 to 37 μs by SDG at 850 °C .…”
mentioning
confidence: 96%
See 2 more Smart Citations